Austerity and the hidden costs of recovery: Inequality and insecurity in the UK households. Issue 4 (December 2016) - Tepe-Belfrage, Daniela; Wallin, Sara
Abstract This introduction to the Special Issue presents research on austerity in British Politics. The work we showcase employs broadly understood gender analysis from different theoretical and disciplinary perspectives to broaden and deepen our understanding of austerity in the United Kingdom. In doing so, it brings to the forefront the meaning of austerity that cannot be deduced from national statistics and mainstream economic accounts: the costs of austerity for British households in their everyday and intergenerational social reproduction. Building upon innovative theoretical work and current empirical research, the contributors interrogate the conflicted rationalities of austerity as a moral and disciplinary form of governance that, ultimately, imposes suffering and inequality especially on the poor.